Prevalence and Course of Thrombocytopenia in Culture Positive and Culture Negative Neonatal Sepsis - Dr. Rabindran; Dr.Hemant Parakh; Dr.Ramesh J K; Dr.Prashant Reddy (Pediatric Review: International Journal of Pediatric Research, 2014)
Introduction: Neonatal Sepsis is commonly associated with thrombocytopenia. Objective: To assess the prevalence and course of thrombocytopenia in culture positive and culture negative neonatal sepsis in comparison to normal newborns. Methods: This is a retrospective case analysis of 533 neonates between January-2012 to December-2014. The parameters examined were Baseline Platelet Count, Change In Platelet Count, (Baseline Platelet Count- Change In Platelet Count)/ Baseline Platelet Count, Platelet Nadir, Incidence, Duration & Severity of Thrombocytopenia. Statistical Analysis: All data were collected in validated preformatted proforma sheet & analysed using appropriate statistical methods. Results: Among 533 neonates, 21.2% had Culture negative sepsis, 9.75% had culture positive sepsis & 69.04% had no sepsis. The prevalence of early onset sepsis was 17.44% & late onset sepsis was 13.50%. About 24.76% babies had thrombocytopenia; 9.56% had mild thrombocytopenia, 10.13% had moderate & 5.06% had severe thrombocytopenia. Late onset sepsis was associated with significant thrombocytopenia. Culture positive sepsis had significant drop in platelets with lower platelet nadir, higher incidence, more severe & prolonged thrombocytopenia compared to culture negative sepsis & normal neonates. Conclusion: There are quantitative differences in the platelet response to neonatal sepsis, particularly to culture positive sepsis. Hematological changes in platelet count induced by culture proven and culture negative neonatal sepsis can be used to make an early diagnosis and prompt management of neonatal sepsis.